Նախադասության կաղապարների տարաժամանակյա փոփոխությունների առանձնահատկությունները գերմաներենում - Նելլի Խանոյան (ՀՀ ԳԱԱ հրատ.)
In this paper an attempt is made to show the peculiarities of the sentence-models' changes in German, taking as a principle the factor of the linguistic economy, which acquires a special significance for the development, evaluation and for the system-change of the language.
Keywords: Language and Literature; Germanic languages